MANAJEMEN PERUBAHAN: MENGELOLA DIALEKTIKA MANUSIA-ORGANISASI MENJAWAB DINAMIKA LINGKUNGAN (Fokus Ekonomi, 2009)
Problems of change can become small scale or big scope and focus at individual or group of people or one department or division, including organization or one or more s from organizational environment. At conceptual level, management of change problem is the problem of changing to reach the target of like transform, apply and reduce. Analysis  to change at various time will focussed at invention of outcome of change effort, identifying change need to yield outcome.